Rotavirus spreads in a spatially controlled manner - Passarelli, Gianna V.; Doldan, Patricio; Metz Zumarán, Camila; Keser, Yagmur; Boulant, Steeve; Stanifer, Megan (Cells, 2025)
Rotavirus is an enteric virus that leads to 200,000 deaths worldwide every year. The live-cell imaging evaluating rotavirus infection of MA104 cells revealed that rotavirus replication and spread occurs in a spatially controlled manner. Specifically, following initial rotavirus infection, the infected cells die, and the second round of infection occurs in the restricted area surrounding the initially infected cell. Interestingly, we found that the time required to establish the secondary infection is shorter compared to the time required for the initial infection. To determine if this increase in the kinetic of secondary infection was due to the early release of viruses or priming of the cells that are infected during the secondary infection, we used a combination of live-cell microscopy, trypsin neutralization assays, and the pharmacological inhibition of calcium signaling. Together, our results show that the second round of infection required rotavirus to be released and accessible to extracellular proteases. In addition, we found that the calcium wave induced upon rotavirus infection was critical for initial infection but did not play a role in the establishment of a secondary infection. Finally, we uncovered that high viral titers released from the initial infection were sufficient to accelerate the rate of the secondary infection.
Online veröffentlicht am 9. Februar 2025
Gesehen am 04.08.2025